Resolution to Walls Surfaces Condensation & Mould Growth Issue in an 24-hours Air Conditioned Room - Cheah, Yee Hong; Gan, Chin Yeow; Hong, Ching Wah; Momin, Nor Jamiiadd (2015)
The aim of the project is Lo resolve the condensation and mould growth issues in a 24-hours air conditioned room. With the boundary conditions provided, a solution to optimize the design of insulation panel and installation method to prevent condensation and mould growth is proposed.